Ensaio sobre a natureza humana: uma reflexão a partir de Abraham Maslow - Jonas Muriel Backendorf (Inquietude)
This paper presents some thoughts about who we are as humans, a task that fits in the field of moral psycology, specifically in the areas which aims understanding and defineing more broadly the moral subject or agent. The perspective adopted here is that of the American Abraham Maslow, whose work is focused on the defense of a human nature endowed with high potential and in a sense neglected by the Western tradition. Regarding its methodology, it is hard to define the author’s approach, but in general terms it has a phenomenological aspect. Nevertheless, it is studyed here for its contributions to a realistic ethical theory focused on a comprehensive understanding of our concrete moral life.